Pentingnya Kepemimpinan Dalam Implementasi Manajemen Mutu Terpadu - Nur Mu’alina; Muhammad Husain; Rizqi Nur Faizin (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
Leadership plays an important role in the success of an educational institution. Leadership is based on the nature of a person who is able to influence other people to achieve common goals. The quality of education always refers to the specifications of educational services that are in accordance with the objectives or benefits of the education itself. The purpose of this research is to determine the importance of leadership in improving the quality of education in Indonesia. The method used by researchers is literature study from various journals. The results of the research are facts regarding the importance of team leadership in the successful implementation of total quality management.